Transcription of HIV-1 at sites of intact latent provirus integration - Teixeira, Ana Rafaela; Bittar, Cintia; Silva Santos, Gabriela S.; Oliveira, Thiago Y.; Huang, Amy S.; Linden, Noemi; Ferreira, Isabella A.T.M.; Murdza, Tetyana; Mücksch, Frauke; Jones, R. Brad; Caskey, Marina; Jankovic, Mila; et al. (Journal of experimental medicine, 2024)
HIV-1 antiretroviral therapy is highly effective but fails to eliminate a reservoir of latent proviruses, leading to a requirement for life-long treatment. How the site of integration of authentic intact latent proviruses might impact their own or neighboring gene expression or reservoir dynamics is poorly understood. Here, we report on proviral and neighboring gene transcription at sites of intact latent HIV-1 integration in cultured T cells obtained directly from people living with HIV, as well as engineered primary T cells and cell lines. Proviral gene expression was correlated to the level of endogenous gene expression under resting but not activated conditions. Notably, latent proviral promoters were 100-10,000× less active than in productively infected cells and had little or no measurable impact on neighboring gene expression under resting or activated conditions. Thus, the site of integration has a dominant effect on the transcriptional activity of intact HIV-1 proviruses in the latent reservoir, thereby influencing cytopathic effects and proviral immune evasion.
Gesehen am 15.10.2024